PENGARUH GLOBALISASI TERHADAP PERKAWINAN ENDOGAMI DI DESA TENGANAN PEGRINGSINGAN KABUPATEN KARANGASEM - Anom, I Gusti Ngurah (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
Tenganan Pagringsingan, grow and develop with the impression of the original as the village of Bali Aga, the village that has a pattern of life and governance communities based on the regulation of Traditional Adat Village who inherited their ancestors, including the system of marriage that has a style endogamy, As stated in awig awig